Interactive DC-DC converters tools for instant design and education - Gonçalves, Flávio A. S. [UNESP]; Sampaio, Leonardo P. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
This paper deals with the usage of interactive simulations tools to serve as an oriented design tool for the lectures and laboratory experiments in the power electronics courses. A dynamic and interactive visualization of simulations for idealized converters in steady state are provided by the proposed educational tools, allowing students to acquire qualification in non-isolated DC-DC converters, without previous circuitry knowledge, either without the usage of sophisticated simulation packages. The interaction with proposed simulation tools can be accomplished by student using direct or graphic mode. In direct mode the parameters related with the design of converter can be inserted simply editing default values presented in textboxes, while in the graphic mode students interact indirectly with design information by manipulating visual widgets. In order to corroborate the proposed interactive simulation tools, comparisons of results from buck-boost and boost converters on proposed tools and a well-known simulator package with those on experimental evaluation from laboratory classes were presented. © 2009 IEEE.
Keywords: DC-DC converter design; DC-DC converter simulation; Education methodology; Education tool; Simulation; BOOST converter; Buck-boost; Default values; Design information; Design tool; Direct mode; Educational tools; Experimental evaluation; Interactive simulations; Interactive visualizations; Laboratory class; Laboratory experiments; Power electronics course; Simulation education; Simulation packages; Simulation tool; Simulator package; Steady state; Curricula; Design; HVDC power transmission; Power electronics; Students; Tools; DC-DC converters